Does the bracket–ligature combination affect the amount of orthodontic space closure over three months? A randomized controlled trial. (June 2013) - Wong, Henry; Collins, Jill; Tinsley, David; Sandler, Jonathan; Benson, Philip
<x xml:space="preserve">Abstract</x> Objective: To investigate the effect of bracket–ligature combination on the amount of orthodontic space closure over three months. Design: Randomized clinical trial with three parallel groups. Setting: A hospital orthodontic department (Chesterfield Royal Hospital, UK). Participants: Forty-five patients requiring upper first premolar extractions. Methods: Informed consent was obtained and participants were randomly allocated into one of three groups: (1) conventional pre-adjusted edgewise brackets and elastomeric ligatures; (2) conventional pre-adjusted edgewise brackets and Super Slick® low friction elastomeric ligatures; (3) Damon 3MX® passive self-ligating brackets. Space closure was undertaken on 0·019×0·025-inch stainless steel archwires with nickel–titanium coil springs. Participants were recalled at four weekly intervals. Upper alginate impressions were taken at each visit (maximum three). The primary outcome measure was the mean amount of space closure in a 3-month period. Results: A one-way ANOVA was undertaken [dependent variable: mean space closure (mm); independent variable: group allocation]. The amount of space closure was very similar between the three groups (1 mm per 28 days); however, there was a wide variation in the rate of space closure between individuals. The differences in the amount of space closure over three months between the three groups was very small and non-significant (P = 0·718). Conclusion: The hypothesis that reducing friction by modifying the bracket/ligature interface increases the rate of space closure was not supported. The major determinant of orthodontic tooth movement is probably the individual patient response.